Safety and Preliminary Immunogenicity of Recombinant Hepatitis B (Bio Farma) Vaccine in Adults and Children: A Phase 1 Clinical Trial - Fadlyana, Eddy; Tarigan, Rodman; Rusmil, Kusnandi; Sari, Rini Mulia; Kartasmita, Cissy B; Mardiah, Behesti Zahra; Dwi Putra, Muhammad Gilang (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: In order to fulfil the requirements of the national immunization program and sustain the production capacity of the monovalent Hepatitis B vaccine, this study aimed to assess the safety and immunogenicity of the recombinant Hepatitis B Vaccine (Bio Farma) using the new Hepatitis B bulk. Methods: This study was an experimental, randomized, double-blinded, and controlled Phase I clinical trial, with 100 healthy subjects divided into 50 adults and 50 adolescents. Subjects were randomly assigned to receive either the Bio Farma registered Recombinant Hepatitis B Vaccine (group A) or a new source of Hepatitis B bulk (group B). Subjects received one or three doses of vaccine, depending on the baseline anti-Hbs titer. Subjects were given diary cards to record solicited and unsolicited adverse events for 28 days following vaccination. Vaccine immunogenicity was assessed by measuring the level of HBsAg antibody titer elevation.Results: No serious adverse events were reported during clinical trials. The frequencies of adverse events were not significantly different between the two vaccine-randomized groups. The most immediately observed local reaction was local pain, reported by 35.7–42.8% of adults and 24.0–26.3% of adolescents, without any systemic reactions. Seroconversion in adults in group B reached 100% and 78.5% in group A, meanwhile in adolescent subjects in both groups it reached 100%. A substantial increase in geometric mean titer (GMT) was observed in the majority of subjects after immunization.Conclusion: Recombinant Hepatitis B Vaccine with a new source of HBsAg B bulk is safe, well tolerated, and highly immunogenic.